Antimicrobial studies of cosmos caudatus kunth. (Compositae) - Md Rasdi, Nor Hafipah; Abd. Samah, Othman; Sule, Abubakar; Ahmed, Qamar Uddin (Academic Journals, 2010)
The present study aims to investigate crude n-hexane, diethyl ether (Et2O), ethanol (EtOH) and phosphate buffered saline (PBS) extracts of Cosmos caudatus Kunth leaves for their antimicrobial potential against 5 microbial strains comprising 2 Gram positive bacteria: Bacillus subtilis, Staphylococcus aureus, 2 Gram negative bacteria: Escherichia coli, Pseudomonas aeruginosa and 1 fungi: Candida albicans by the disc diffusion method. Preliminary antimicrobial screening showed inhibition by the n-hexane, diethyl ether, and ethanol extracts against all the tested microbes, however the phosphate buffered saline extract was inactive against Bacillus subtilis and Staphylococcus aureus. MIC values ranging from 6.25 - 25 mg/ml for the tested crude extracts were obtained by the microtiter plate method. This study showed that the crude extracts of the leaves of C. caudatus Kunth. could be potential source of new antimicrobial agents especially to treat infections caused by the tested microbial strains and confirms its utility in folk medicines.